Langston Hughes - Hughes, Langston, 1902-1967.; Rampersad, Arnold; Roessel, David E. (David Ernest), 1954-; Andrews, Benny, 1930-2006. (New York : Scholastic, 2006)
A brief profile of African American poet Langston Hughes accompanies some of his better known poems for children.
Negro speaks of rivers -- Aunt Sue's stories -- Danse Africaine -- Mother to son -- When Sue wears red -- My people -- Youth -- Dream variations -- Dream keeper -- Walkers with the dawn -- I, too -- Weary blues -- Homesick blues -- Hey! -- Hey! Hey! -- Afro-American fragment -- Genius child -- Note on commercial theatre -- Merry-go-round -- Words like freedom -- Still here -- I dream a world -- Final curve -- Theme for English -- Harlem -- Drums.
"This edition is only available for distribution through the school market"--P. [4] of cover.
Includes index.
Keywords: African Americans -- Juvenile poetry; Children's poetry, American